KOMPARASI PEMODELAN REGRESI OLS GAUSSIAN, BETA DAN REGRESI FRACTIONAL PADA DATA RASIO - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Ni Komang Semara Yanti; Putu Pande Wahyu Diatmika; Nurhidayati Nurhidayati; Sigit Budiantono (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
The Public Health Development Index (PHDI) is an indicator that describes health problems and plays a role in efforts to increase long and healthy life expectancy. This study aims to compare PHDI modeling in 35 City Districts of Central Java Province using Gaussian-based regression (OLS), beta regression and fractional regression. The independent variables used are the percentage of poor people and the percentage of households accessing proper sanitation. Data is sourced from the Ministry of Health and Central Java Statistics Agency. All three models gave the same results for both simultaneous and partial tests in modeling PHDI modeling cases. Fractional regression models provide the best results with the smallest error value criteria (AIC and BIC). The percentage of poor people has a significant negative effect on IPKM while the percentage of proper sanitation has a significant positive effect on PHDI. Based on these results, it is expected that policy makers can provide comprehensive and targeted policies in improving PHDI in Indonesia